2023
DOI: 10.1002/ece3.9967
|View full text |Cite
|
Sign up to set email alerts
|

Using quantile regression and relative entropy to assess the period of anomalous behavior of marine mammals following tagging

Abstract: Tagging of animals induces a variable stress response which following release will obscure natural behavior. It is of scientific relevance to establish methods that assess recovery from such behavioral perturbation and generalize well to a broad range of animals, while maintaining model transparency. We propose two methods that allow for subdivision of animals based on covariates, and illustrate their use on narwhals ( Monodon monoceros ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Shuert et al, 2021). On the other hand, significant inter-individual variability in the magnitude of the response was observed (Nielsen et al, 2023;Shuert et al, 2021). Most individuals appeared to recover in the first 8-9 hours following release (Nielsen et al, 2023;Shuert et al, 2021).…”
Section: Narwhalmentioning
confidence: 96%
See 3 more Smart Citations
“…Shuert et al, 2021). On the other hand, significant inter-individual variability in the magnitude of the response was observed (Nielsen et al, 2023;Shuert et al, 2021). Most individuals appeared to recover in the first 8-9 hours following release (Nielsen et al, 2023;Shuert et al, 2021).…”
Section: Narwhalmentioning
confidence: 96%
“…On the other hand, significant inter-individual variability in the magnitude of the response was observed (Nielsen et al, 2023;Shuert et al, 2021). Most individuals appeared to recover in the first 8-9 hours following release (Nielsen et al, 2023;Shuert et al, 2021). However, both studies have shown that the handling time influences the post-release behaviour, where individuals held for more than 40 minutes (in Shuert et al Preliminary unreported models showed no effect of sex or animal length on cue rates, but the power to find existing differences was unsurprisingly low, so we abstained from presenting those results here.…”
Section: Narwhalmentioning
confidence: 98%
See 2 more Smart Citations